2017
DOI: 10.1038/srep44345
|View full text |Cite
|
Sign up to set email alerts
|

Correction: Corrigendum: Gene expression differences in Longissimus muscle of Nelore steers genetically divergent for residual feed intake

Abstract: Scientific Reports 6: Article number: 39493; published online: 22 December 2016; updated: 05 April 2017 This Article contains an error in the order of the Figures, where Figures 2 and 3 were inverted. The correct Figures 2 and 3 appear below:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…As an indicator, RFI is independent of growth traits such as average daily gain (ADG) and body weight (BW) (Baker et al, 2006) and is mainly related to economic traits such as dry matter intake (DMI) and feed conversion efficiency (FCR) (Gomes et al, 2012). Recently, pathways such as adenosine 5′monophosphate (AMP)-activated protein kinase (AMPK) signaling (Karisa et al, 2014), metabolic pathways and oxidative stress (Tizioto et al, 2017), lipid metabolism (Tizioto et al, 2015), and the immune response (Gondret et al, 2017) were reported to be involved in RFI variance. Moreover, genes such as COL14A1 (de Lima et al, 2020), OGN (Vigors et al, 2019), ACE (Yi et al, 2015), and SMCT (de Lima et al, 2020) and quantitative trait loci such as EFEMP1 (de Lima et al, 2020) and SHC3 (Weber et al, 2016) were also identified to be potentially related with RFI.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As an indicator, RFI is independent of growth traits such as average daily gain (ADG) and body weight (BW) (Baker et al, 2006) and is mainly related to economic traits such as dry matter intake (DMI) and feed conversion efficiency (FCR) (Gomes et al, 2012). Recently, pathways such as adenosine 5′monophosphate (AMP)-activated protein kinase (AMPK) signaling (Karisa et al, 2014), metabolic pathways and oxidative stress (Tizioto et al, 2017), lipid metabolism (Tizioto et al, 2015), and the immune response (Gondret et al, 2017) were reported to be involved in RFI variance. Moreover, genes such as COL14A1 (de Lima et al, 2020), OGN (Vigors et al, 2019), ACE (Yi et al, 2015), and SMCT (de Lima et al, 2020) and quantitative trait loci such as EFEMP1 (de Lima et al, 2020) and SHC3 (Weber et al, 2016) were also identified to be potentially related with RFI.…”
Section: Introductionmentioning
confidence: 99%
“…RNA sequencing (RNA-seq) has previously been used to detect gene expression associated with divergent RFI in cattle. Researchers have identified several RFI-related genes and pathways from cattle liver (Tizioto et al, 2017), skeletal muscle (Khansefid et al, 2017), blood (Xi et al, 2015), adipose tissue (Weber et al, 2016), and rumen epithelium (Kong et al, 2016). However, the reported differentially expressed genes (DEGs) differed significantly among studies, likely due to differences in breeds, age, sex, and tissue.…”
Section: Introductionmentioning
confidence: 99%
“…RFI is a complex quantitative trait controlled by polygenes [ 30 ], and it determines the development of the beef cattle industry. As an important economic trait, researchers have tried to uncover the signaling molecules associated with the trait in different tissues such as liver [ 14 ], skeletal muscle [ 15 ], blood [ 16 ], adipose tissue [ 17 ], rumen epithelium [ 18 ], duodenum [ 2 ]. However, the characteristics and commonalities of RFI in different breeds of beef cattle are not well understood.…”
Section: Discussionmentioning
confidence: 99%
“…Potential mechanisms of phenotypic regulation by specific genes can be revealed using transcriptome sequencing technologies (such as KLF6 [12,13]), but most studies of RFI have focused on gene expression in one or two tissues of a breed [2,[14][15][16][17][18]. In different studies, differences in experimental conditions (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…However, the specific mechanisms underlying the biology of RFI are still underdeveloped. Plenty of experimenters have endeavored to elucidate RFI variation in terms of gene expression from a single tissue [e.g., liver ( 23 ), skeletal muscle ( 24 ), blood ( 25 ), adipose tissue ( 26 ), rumen epithelium ( 27 ), duodenum ( 5 )]. As each study has focused on only individual tissue, it is highly variable and couldn't acquire a coherent conclusion ( 28 ).…”
Section: Introductionmentioning
confidence: 99%